PENGARUH GCG DAN CSR TERHADAP PROFITABILY DAN COMPANY VALUE SEBAGAI VARIABEL MODERATING - Nunuk Novianti; Dini Fitrianti (Unversitas Prof. Dr. Moestopo (Beragama), 2022)
This study aims to determine the effect of Good Corporate Governance (GCG) and Corporate Social Responsibility (CSR) on profitability and company value as moderating variables in the IDX plastic manufacturing companies. The population in this study was obtained using the purposive sampling method for plastic manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2021 period and a sample of 5 research companies. The analytical method used is multiple linear regression analysis with the SPSS 26 (Statistical Product and Service Solution) application tool. The results of the study show that Good Corporate Governance has no effect on profitability. Corporate Social Responsibility affects profitability. Company value is not able to moderate Good Corporate Governance on profitability. Company value is not able to moderate Corporate Social Responsibility on profitability.